How do CuO sheets (sh-CuO) enable efficient chlorinated hydrocarbon removal?. (December 2022) - Farooq, Usman; Wang, Fei; Aslam, Malik Muhammad Arslan; Wang, Xinhai
Abstract: The presence of additional active sites in a synthesized heterogeneous material is crucial for the activation of peroxymonosulfate (PMS). The prepared CuO sheets ( sh- CuO) were utilized in the PMS process to degrade trichloroethane (TCA). Various characterizations (SEM, TEM, XRD, and XPS) revealed monoclinic tenorite CuO irregular rectangular sheets (0.72 × 0.28 μm) with an 82 % crystallinity and mesoporous structure. The sh- CuO showed enhanced (93 %) heterogeneous activation of PMS for TCA oxidation compared to commercially available CuO (43 %) and Co3 O4 (47 %). The experimental parameters study such as PMS, sh -CuO dose, temperature, and pH confirmed that sh -CuO possessed low activation energy (9.601 kJ/mol) which strengthened its performance around acidic pH. The mechanism study revealed that due to its high redox potential, not only SO4 − radicals but also Cu 3+ contributed as a powerful oxidant. Finally, the sh -CuO stability and recyclability of 86 % until the fourth cycle supported its potential application in groundwater remediation. Graphical abstract: Unlabelled Image Highlights: Facile hydrothermal synthesis of CuO sheet ( sh -CuO). The performance of sh -CuO material is far better than commercially available counterparts. Mechanism revealed not only radicals but also Cu 3+ played its role in trichloroethane (TCA) degradation. The sh -CuO performed an environmentally benign and stable catalyst for TCA degradation.